ANALYTICAL STUDY OF SALIVARY MMP-12 EXPRESSION IN ORAL SUBMUCOUS FIBROSIS - Saleem, Zohra; Shaikh, Abdul Hafeez; Majeed, Muhammad Mansoor; Ahmed, Shaheen; Zaman, Uzma; Siddiqui, Zarah; Kazmi, Anum (Journal of Ayub Medical College Abbottabad, 2022)
Background: Oral submucous fibrosis (OSF) is majorly a pathology pertaining to Asian population, reported most in Pakistan, India, Nepal, Bangladesh, and Taiwan. Equilibrium existing between Matrix metalloproteinases (MMP) & tissue inhibitors of matrix metalloproteinases is imperative for the normal integrity of connective tissues. However, this mechanism is disturbed in the presence of OSF, resulting in an increase in the extracellular matrix. Methods: It is an analytical study including two groups with a total of 60 participants. The first group consists of 30 healthy participants and the other group consists of 30 patients presenting with oral submucous fibrosis. Collected samples of saliva were stored at -80 °C after centrifugation. For ELISA investigation, the procedure was performed as per manufacturer’s instruction. Salivary matrix metalloproteinases- 12 concentration was estimated with the help of a standard curve. Data was analysed using SPSS 23. Mann Whitney test was applied to determine the difference existing in Matrix metalloproteinases- 12 levels between healthy and Oral submucous fibrosis participants. p-value <0.05 was contemplated as significant. Results: Statistical investigation indicated significant difference in Matrix metalloproteinases- 12 levels between Oral submucous fibrosis and healthy group (p<0.05). Saliva samples obtained from oral submucous fibrosis patients demonstrated raised concentrations of Matrix metalloproteinases- 12 as compared to healthy participants. Conclusion: Our study demonstrates significant upsurge in Matrix metalloproteinases- 12 expression in samples of saliva obtained from oral submucous fibrosis patients as compared to healthy individuals. Therefore, salivary Matrix metalloproteinases- 12 could serve as a useful diagnostic marker for OSF.